Hydrophobic stretchable polydimethylsiloxane films with wrinkle patterns prepared via a metal‐assisted chemical etching process using a Si master mold. Issue 19 (17th December 2020) - Lee, Hanbin; Chae, Sangmin; Yi, Ahra; Kim, Hyo Jung
Abstract: We fabricated hydrophobic, stretchable, wrinkle‐patterned polydimethylsiloxane (PDMS) films via a metal‐assisted chemical etching (MACE) process using a Si master mold, which is a mask‐free technique for fabricating large‐area films. The wrinkle‐patterned PDMS surface prepared via MACE exhibited high hydrophobicity and stretchability, which are difficult to achieve with wrinkle‐patterned PDMS prepared via a conventional process, such as, plasma treatment, e‐beam, or laser patterning. The contact angle of the wrinkled PDMS surface was dependent on the size of the micro/nanostructures, and the largest contact angle was 135.8 ± 0.1° for the film prepared under the optimum conditions. To confirm the applicability of the wrinkled PDMS films to flexible electronics, we tuned the mechanical properties by controlling the crosslinker ratio in the films. The Young's modulus ranged from 0.193 to 1.364 MPa depending on the crosslinker ratio, and the stress of the optimum film was 1.5 MPa under 250% strain. Abstract : The nanoporous structure was fabricated in a Si master mold through the MACE(Metal assisted chemical etching) process and successfully replicated on the PDMS surface. The final form of PDMS was the surface of the micro/nano wrinkle pattern, with increased hydrophobicity compared to flat PDMS. The hydrophobicity of wrinkle‐patterned PDMS was maintained when expanded up to 250%.